The Implementation of character education in shaping students’ moral character - Aprilia, Anisa (Maliki Interdisciplinary Journal, 2026)
This study examines how character education is implemented to shape student morality in a university environment. Higher education serves not only as a place to develop knowledge and work skills, but also as an important place to shape moral attitudes, personality, and social responsibility in the younger generation. Character education at universities is carried out by integrating moral, social, and religious values ​​into the curriculum, teaching methods, student activities, campus culture, and good examples from lecturers and staff. Key supporting factors include a religious and disciplined campus environment, role models set by lecturers, family support, and positive social interactions. On the other hand, key obstacles come from the influence of social media, promiscuity, lack of awareness among students, and weak collaboration between the campus, family, and community. The impact of character education can be seen in increased discipline, honesty, responsibility, courtesy, social awareness, and ethics in using digital media. Furthermore, character education also helps reduce negative behaviors such as plagiarism, misuse of technology, and intolerance. This study emphasizes the importance of strengthening character education regularly and continuously. This is considered an important part of the mission of higher education to form citizens who have integrity and good morals.